1993
DOI: 10.1164/ajrccm/147.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Site of Pharyngeal Narrowing Predicts Outcome of Surgery for Obstructive Sleep Apnea

Abstract: Uvulopalatopharyngoplasty (UPPP), an operation that enlarges the pharyngeal airway at the level of the soft palate, improves respiratory status during sleep in only 50% of patients with obstructive sleep apnea (OSA). This poor outcome suggests that narrowing of the pharyngeal airway at nonpalatal sites contributes to the obstructive process in many patients with OSA. We have used a novel endoscopic method to identify regions of the passive pharyngeal airway most susceptible to narrowing or complete closure. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 35 publications
4
83
0
4
Order By: Relevance
“…The key to successful oral appliance therapy is consistency between the site of upper airway occlusion during sleep and the mechanical action of the appliance. A number of reports have suggested that OSA patients show both a single site of upper airway narrowing at the velopharynx and multilevel upper airway collapse during sleep [18][19][20][21][22][23]. If the site of occlusion is extended to below the level of the velopharynx (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The key to successful oral appliance therapy is consistency between the site of upper airway occlusion during sleep and the mechanical action of the appliance. A number of reports have suggested that OSA patients show both a single site of upper airway narrowing at the velopharynx and multilevel upper airway collapse during sleep [18][19][20][21][22][23]. If the site of occlusion is extended to below the level of the velopharynx (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, obesity, jaw position, acromegaly, tonsillar hypertrophy, and a smaller bony enclosure surrounding the pharynx have been demonstrated to predispose toward pharyngeal collapsibility. 23,[32][33][34][35][36] These studies imply that upper airway structural differences distinguish OSA patients from normal subjects, and may predispose to upper airway obstruction when protective neuromuscular mechanisms wane at sleep onset. 37 Obesity, the major risk factor for OSA, has been linked with elevations in neck circumference and increased amounts of peripharyngeal fat, 38,39 which could narrow and compress the upper airway.…”
Section: Contribution Of Anatomic Factors To Osamentioning
confidence: 96%
“…This is based on EMG studies performed in adults (11), as well as studies performed by us in school-aged children using the same techniques (9). Infants have been shown to have a much more rapid upper airway response to drops in negative pressure; thus, the results of this study cannot be extrapolated to infants with OSAS (9,30,31).…”
Section: Pfrmentioning
confidence: 99%